2022
DOI: 10.1017/erm.2022.22
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related genomic instability and altered xenobiotic metabolism: possible consequences for cancer risk and chemotherapy

Abstract: The increase in the prevalence of obesity has led to an elevated risk for several associated diseases including cancer. Several studies have investigated the DNA damage in human blood samples and showed a clear trend towards increased DNA damage in obesity. Reduced genomic stability is thus one of the consequences of obesity, which may contribute to the related cancer risk. Whether this is influenced by compromised DNA repair has not been elucidated sufficiently yet. On the other hand, obesity has also been li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Although the comet assay, after an analysis of a huge registry/database of more than 19,000 individuals, has established certain values for healthy, cancer-free, cancer-prone, and deceased populations (the ones that will be in the mortality registry) [ 18 , 19 ], the micronucleus cytome assay has not been fully explored with all its parameters, usually only for MN frequency [ 21 , 25 , 27 , 60 ]. As can be seen in the mentioned reviews, although both assays demonstrated a positive connection between elevated MN frequency and comet assay parameters and obesity, studies and results are still scarce, with very little data on the severely obese without studies using both assays on the severely obese in those reviews [ 21 , 25 , 27 , 60 ]. Considering that NBs are a biomarker of gene amplification, NPBs are a biomarker of di-centric chromosomes and can demonstrate different types of DNA damage in comparison to the MN assay, which is a biomarker of whole/or partial chromosome loss.…”
Section: Discussionmentioning
confidence: 99%
“…Although the comet assay, after an analysis of a huge registry/database of more than 19,000 individuals, has established certain values for healthy, cancer-free, cancer-prone, and deceased populations (the ones that will be in the mortality registry) [ 18 , 19 ], the micronucleus cytome assay has not been fully explored with all its parameters, usually only for MN frequency [ 21 , 25 , 27 , 60 ]. As can be seen in the mentioned reviews, although both assays demonstrated a positive connection between elevated MN frequency and comet assay parameters and obesity, studies and results are still scarce, with very little data on the severely obese without studies using both assays on the severely obese in those reviews [ 21 , 25 , 27 , 60 ]. Considering that NBs are a biomarker of gene amplification, NPBs are a biomarker of di-centric chromosomes and can demonstrate different types of DNA damage in comparison to the MN assay, which is a biomarker of whole/or partial chromosome loss.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, obesity can affect the expression of hepatic and intestinal drug transporters, which can affect drug uptake and excretion 64 . Obesity can alter the activity and expression of several Phase I (oxidation, reduction, hydrolysis) cytochrome P450 (CYP) enzymes, including CYP1A2, CYP2C9, CYP2C19, CYP2D6, CYP3A4, and CYP2E1 68 . Although the results of the effect of obesity on hepatic drug metabolizing enzymes vary, overall obesity decreases the activity of CYP2C19, 69 while increasing the activity of CYP2C9, CYP2C92E1, and CYP2C93A4 68 .…”
Section: Effect Of Obesity On Small‐molecule Anticancer Drugsmentioning
confidence: 99%
“…Obesity can alter the activity and expression of several Phase I (oxidation, reduction, hydrolysis) cytochrome P450 (CYP) enzymes, including CYP1A2, CYP2C9, CYP2C19, CYP2D6, CYP3A4, and CYP2E1 68 . Although the results of the effect of obesity on hepatic drug metabolizing enzymes vary, overall obesity decreases the activity of CYP2C19, 69 while increasing the activity of CYP2C9, CYP2C92E1, and CYP2C93A4 68 . Obesity is also associated with enhanced capacity for Phase II hepatic drug metabolism including N ‐acetylation, sulfation, and glucuronidation 70,71 …”
Section: Effect Of Obesity On Small‐molecule Anticancer Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly enough, increased adiposity appears to hamper cancer cell response to chemotherapy by reducing fatty acid oxidation involved in DNA damage repair, ultimately decreasing cell death. This is not unexpected given the fact that adiposity would be expected to affect various aspects of drug metabolism, and therefore could influence drug distribution, treatment response, and adverse effects [8]. Additionally, obesity is associated with an increased risk of complications during surgery and radiation therapy [9].…”
mentioning
confidence: 99%